2005
DOI: 10.2320/matertrans.46.1004
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Rust Formation Process on Fe–Cr and Fe–Ni Alloys under Wet/Dry Cycles Observed by Synchrotron Radiation X-ray Diffraction

Abstract: In situ observation of initial process of rust formation on Fe-5 mass%Cr and Fe-9 mass%Ni alloys using SPring-8 synchrotron radiation was carried out under wet/dry cycling with 3.5% Na 2 SO 4 and NaCl solution films. It was shown that the rust constituents detected during the quite initial wet/dry cycles were Fe(OH) 2 and Fe(OH) 3 independent of alloying elements. Most characteristic X-ray diffraction peaks obtained under the Na 2 SO 4 solution film are indexed as those from goethite, -FeOOH, both in the Fe-Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Due to these two different types of binding, akaganeite possesses a tunnel in its structure. The structure of akaganeite stabilizes if the center of the tunnel is occupied with Cl ¹ , 16,17) indicating that akaganeite can be formed under the simulated sulfuric acid mist environment containing chlorides. However, peaks derived from akaganeite were smaller than those from goethite and magnetite.…”
Section: A D V a N C E V I E Wmentioning
confidence: 99%
“…Due to these two different types of binding, akaganeite possesses a tunnel in its structure. The structure of akaganeite stabilizes if the center of the tunnel is occupied with Cl ¹ , 16,17) indicating that akaganeite can be formed under the simulated sulfuric acid mist environment containing chlorides. However, peaks derived from akaganeite were smaller than those from goethite and magnetite.…”
Section: A D V a N C E V I E Wmentioning
confidence: 99%
“…tion of 0.1 kmol/m 3 . Yamashita et al 15) observed rust formation processes using synchrotron radiation X-rays and showed that -FeOOH was preferentially formed under the effect of SO 4 2À ion. Moreover, it was pointed out that Cr become a nucleus for the growth of -FeOOH 16) because Cr is less soluble in -FeOOH than in -FeOOH.…”
Section: °8°10°12°14°16°18°20°-mentioning
confidence: 99%